2002
DOI: 10.1120/jacmp.v3i2.2576
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric parameters of three new solid core I‐125 brachytherapy sources

Abstract: Monte Carlo calculations and TLD measurements have been performed for the purpose of characterizing dosimetric properties of new commercially available brachytherapy sources. All sources tested consisted of a solid core, upon which a thin layer of normalI125 has been adsorbed, encased within a titanium housing. The PharmaSeed BT‐125 source manufactured by Syncor is available in silver or palladium core configurations while the ADVANTAGE source from IsoAid has silver only. Dosimetric properties, including the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
4
11
0
Order By: Relevance
“…However, Λ from this study agrees with MC and TLD results reported by Solberg et al (25) within 0.4 and 0.2% respectively and to within 0.1% of recent work by Taylor and Rogers, (17) using point voxel scoring cells. When compared with Λ, calculated using WAFAC voxel scoring cells, Λ from this study is 3.6% higher (17) .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, Λ from this study agrees with MC and TLD results reported by Solberg et al (25) within 0.4 and 0.2% respectively and to within 0.1% of recent work by Taylor and Rogers, (17) using point voxel scoring cells. When compared with Λ, calculated using WAFAC voxel scoring cells, Λ from this study is 3.6% higher (17) .…”
Section: Resultssupporting
confidence: 92%
“…When compared with more recent work by Taylor and Rogers (17) and Aryal et al, (26) the agreement is much better ranging from 0.1% to 1.9% and 0.2% to 4.8%, respectively. The difference between the consensus gL(r) values and recent work, including this study, is primarily due to the different cross‐section libraries and photon energy spectra used, as described by Aryal et al (26) The outdated photoelectric cross sections used by Solberg et al (25) were the XCOM tabulation of Berger and Hubbell (30) and the 125I decay spectrum was taken from that of Attix (31) . This study used the MCNP default 04p cross‐section library, based upon ENDF/B‐VI Release 8 Photoatomic Data, (32) and the NNDC decay spectrum (18) …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The uncertainty of the experimental method became larger when the measured distance from the seed was small owing to the high gradient dose distribution near the radioactive seed. The Monte Carlo results of g ( r ) for the GMS BT‐125‐1 125 I seed were found in agreement (within 3.3%) with corresponding results for the PharmaSeed BT‐125‐2 125 I seed 29. However, it is different from PharmaSeed BT‐125‐1 125 I seed and Model 6711 125 I seed due to the different structures and materials of the seeds used in the Monte Carlo simulation.…”
Section: Discussionsupporting
confidence: 66%